Respostas

2013-07-03T14:39:05-03:00

√(x+1) + √(3x) = 5 

√(x+1)= 5-√(3x)

(√(x+1))²=(5-√(3x))²

x+1=25-10√(3x)+3x

x+1-25-3x=-10√(3x)

2x+24=10√(3x)

(2x+24)²=(10√(3x))²

4x²+96x+576=300x

4x²-204x+576=0

2x²-102x+288=0

x²-51x+144=0

delta=2601-576

delta=2025

x=(51+/-45)/2

x1=48

x2=3

como temos raízes envolvidas na equação teremos que conferir os resultados:

√(48+1) + √(3(48)) = 5 

√(49) + √(144) = 5 

7+12=5

19=5   falso

 

√(3+1) + √(3(3)) = 5

√(4) + √(9) = 5  

2+3=5

5=5 verdadeiro

resposta: x=3

1 5 1